Formulation of edible film mucoadhesive cinnamon extract (Cinnamomum burmanni) - Jamilatun, Makhabbah; Lukito, Pradea Indah (Sasambo Journal of Pharmacy, 2025)
Antioxidants can neutralize free radicals, playing a role in preventing degenerative diseases. Cinnamon has very strong antioxidant activity. Edible film can function as carriers of antioxidant compounds. This research was conducted to determine the physical quality and antioxidant activity of cinnamon extract mucoadhesive edible film. The research method used is quantitative experimental. There are four edible film mucoadhesive formulas with different concentrations of cinnamon extract added, namely 0% at F0, 5% at F1, 10% at F2 and 15% at F3. The test results for organoleptic F0 are clear white, odorless, thin, and sticky sheets, pH 7.54; thickness 0.026 mm; weight uniformity 30.93; water content 32.61%. The organoleptic test results for F1 are dark brown, have a typical cinnamon smell, are thin and non-sticky sheets, pH 6.78; thickness 0.063 mm; weight uniformity 30.52; water content 17.32%. The organoleptic test results for F2 are dark brown, have a typical cinnamon smell, are thin and non-sticky sheets, pH 6.21; thickness 0.073 mm; weight uniformity 24.53; water content 12.81%. The organoleptic test results for F3 are dark brown, have a typical cinnamon smell, are thin and non-sticky sheets, pH 6.29; thickness 0.08 mm; weight uniformity 15.42; water content 15.74%. The antioxidant activity was weak in F0, very strong in F1, F2, and F3.  Edible film mucoadhesive cinnamon extract in formulas F1, F2, and F3 produces good physical properties according to standards and has very strong antioxidant activity. The conclusion of this study shows that cinnamon extract can be formulated into Edible Film Mucoadhesive, as seen from its antioxidant activity in F3, with an extract concentration of 15%.